Democracia e concerto americano : a visão de O Cruzeiro sobre a Argentina nas relações interamericanas (1946-1966) - Dalmáz, Mateus (2014)
Largest magazine in circulation and movement in Brazil between the 1940s and 1950s, O Cruzeiro has published a variety of subjects in its 47 years of existence, including international politics. One theme in particular caught the attention about the number of publications: Argentina's participation in interamerican relations between forty and sixty years. The central objective of the research is to analyze the critical periodic over Argentina in American international concert from 1946, the beginning of the Perón s government, and 1966, end of President Arturo Illia s government. Faced with questions about the symbolic significance of the material, the argue is that the hypothesis that the columns and photo reports of the weekly meet the ideological function of defending democracy and political and economic continental concert. The examination of relations between Argentina and America in general, and Brazil in particular, is made up based on the concept of ideology and relationship between politics and the press informed on Martins (2010), in the field definition journalism on Bourdieu (1997) and the characterization of Brazilian journalism on Ribeiro (2003). The methodology follows the steps of using the media as a source and object of study for history as directed on Barbosa (1998), Elmir (1995) and Zicman (1985). The specific analysis of photo reports is supported primarily on Belting (2010), Joly (2003), Vilches (1997), Mauad and Lopes (2012). It is considered that the ideas of democracy and American integration produced by journalists are comprehensive, admitting the respect and breaking the social contract, in the first case, the U.S. Pan-Americanism and Latin American multilateralism, in the second. It is clear, finally, the featuring of "two Argentinas" in the magazine pages: that of Juan Domingo Perón (disharmony with the inter-american integration and represent a rivarly to Brazil) and protected by the military governments (in line with the relations inter-american and in partnership with Brazil).